Digitalisation, labour and the pandemic: Working life in the post-COVID-19 city. (1st January 2021) - Huws, Ursula; Frapporti, Mattia
Abstract : Introducing this issue, this paper reflects on the role of peer-reviewed research in documenting and analysing the restructuring of labour under rapidly changing global conditions. It summarises the contents of the issue, placing it in the context not only of the 2020-2021 global COVID-19 pandemic, but also in relation to past theoretical debates in the pages of this journal about the dynamics of platform capitalism.